ANALISIS TINGKAT KEPUASAN PASIEN BPJS NON PBI PADA RUMAH SAKIT PEMERINTAH DI KOTA MAKASSAR - Rahmadani, Rahmadani; Indar, Indar; Jam'an, Andi (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2021)
Poor management and health services bpjs health participation provided by the hospital to patients turned out to cause a lot of losses both hospitals and for patients. The purpose of this study is to determine the factors that affect bpjs patient satisfaction with health services. The design of this study is cross sectional study. The population in this study was all BPJS Non PBI patients in the Inpatient Room of Labuang Baji Hospital. Sampling technique is accidental sampling. The measuring instrument used is a questionnaire sheet. Analysis using multiple linear regression. The results showed that there was an influence between reliability (p = 0.002), empathy (p = 0.000), responsiveness (p = 0.037), assurance (p = 0.000), with the satisfaction of inpatient BPJS Non PBI in Labuang Baji Hospital, Makassar City. While the tangible variable (p = 0.545) had no effect on the satisfaction of BPJS Non PBI patients at Labuang Baji Hospital, Makassar City. Based on the results of the logistic regression test, it shows that the empathy variable is the most dominant variable. Keywords : Patient Satisfaction, Empathy, Hospitalization.